Conceptualization of Othering in public health. (30th September 2020) - Akbulut, N; Zick, A; Razum, O
Abstract: Background: Othering refers to various constructed notions of belonging and creates boundaries between Us and Them, which is embedded in power relations. Othering, thus, provides an essential contribution to understanding the link between minority status and health inequalities. So far, Othering is not considered in explanatory models on health inequalities; one reason for this is that Othering for this field of research has not yet been sufficiently investigated either theoretically or empirically. Also, there is no systematic concept that provides well-founded knowledge of the mechanisms of Othering. Methods: A theoretical-analytical investigation was carried out to establish Othering as an analytical concept in public health research. The use of the term Othering varies among research areas. A theoretical framework was developed by drawing insights from a socio-psychological, postcolonial, and intersectional theory. After fundamental differences and similarities of the different theoretical approaches have been worked out, Othering was conceptualized as a multidimensional construct. Results: Othering affects health in different ways as it occurs in multiple dimensions and forms that vary according to marginalized groups and institutional as well as social contexts. Othering takes place as a semantic differentiation between Us and Them and constitutes a material hierarchy within a dominant order of belonging. On this basis, Othering has an inclusive effect by treating Others as a particularly vulnerable group and then offering support to them. Othering also creates social exclusion and reinforces disparity in material resources of othered groups. Exclusions of the Other affect access to material resources such as health, for example, by legitimizing restrictions and access barriers in health care. Conclusions: The developed conceptual framework provides an analytical lens through which the relationship between Othering and public health can be further explored. Key messages: Othering refers to various constructed notions of belonging and difference that engender marginality and structural inequality. Othering can be considered as an essential social determinant of health.